Changes in Temperature and Salinity Tendencies of the Upper Subtropical North Atlantic Ocean at 24.5°N - Vélez-Belchí, Pedro; Hernández-Guerra, Alonso; Fraile-Nuez, Eugenio (Journal of Physical Oceanography, 2010)
Strong interest in multidecadal changes in ocean temperature and heat transport has resulted in the occupation of the North Atlantic Ocean hydrographic transect along 24.5°N five times since 1957, more than any other transoceanic section in the world. This latitude is chosen because it is where the northward ocean transport of heat in the Atlantic reaches its maximum. An analysis of the five oceanographic cruises at this latitude shows that there has been a significant cooling of −0.15°C in the upper ocean (600–1800-dbar range) over the last 7 years, from 1998 to 2004, which is in contrast to the warming of 0.27°C observed from 1957 to 1998. Salinity shows a similar change in tendency, with freshening since 1998. For the upper ocean at 24.5°N, 1998 was the warmest and saltiest year since 1957. Data from the Argo network are used to corroborate the strong cooling and freshening since 1998, showing a −0.13°C cooling in the period between 1998 and 2006 and revealing interannual variability between 2005 and 2008 to be much smaller than the decadal variability estimated using the transect. The results also demonstrate that Argo is an invaluable tool for observing the oscillations in the tendencies of the ocean. Sí